Formulasi Sediaan Losio Ekstrak Etanol Meniran (Phyllanthus niruri L.) Sebagai Penumbuh Rambut Terhadap Tikus Putih (Rattus norvegicus) Jantan Galur Wistar - Luliana, Sri; Desnita, Rise; Sehro, (UI Scholars Hub, 2019)
Meniran (Phyllanthus niruri L.) is a plant used to promote hair growth. In this research, ethanolic extract of P.niruri was formulated into lotion because it was more evenly distributed and non sticky in use compared to cream and gel. The aims of this research is to determine the hair growth activity of the ethanolic extract of P.niruri and the effect of using menthol 1% as an enhancer in lotion formulation. In this research two formula were being tested where Formula I (F1) without menthol 1% and Formula II (F2) with menthol 1%. The 5% of extract was being used in the formulation. The lotion was applied to the rats skin and the hair length was measured on day 7, 14 and 21, while the hair weight was measured on day 21. The results showed that the average hair length on F2 (12.68 3.13 mm) was longer than the F1 (11.21 2.58 mm) although there was no significant difference between both formulas. The average hair weight on F2 (23.00 10.74 mg) was greater that the F1 which was only 15.83 6.11 mg. Both formulas have a longer hair growth activity compared to normal controls (10.74 0.86 mm). It can be concluded that the lotion of ethanolic extract of P. niruri could promote hair growth in white wistar rats and the addition of 1% menthol as an enhancer gave better hair growth activity in F2 group.